GAMBARAN PERILAKU SEKSUAL PRANIKAH PADA MAHASISWA UNIVERSITAS X DI KOTA SEMARANG - Muhammad Yudi Saputra; Kusyogo Cahyo; Aditya Kusumawati (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2018)
In Central Java until March 2016 there were 13.547 HIV cases and 5.049 AIDS cases. Based on that data 9.5% of AIDS patient were teenagers. Beside that many teenagers experienced unwanted pregnancy which caused by promiscuity. From 80 unwanted pregnancies cases at least 50 of them experienced by teenagers aged 13 – 18 years. The purpose of this study is to describe premarital sexual behavior of students at university X.This research is a qualitative research with descriptive approach. Data was collected using in depth interview to 7 research subject with snowball sampling method. Data processing and analysis in validity and reliability form. Validity data is done by triangulation.Subject interviewed were students of X university with range of age 19 – 22. Sexual activity which conducted by the subjects is kissing lips, kissing neck, holding the intimate part of the partner, and having sex. 5 out of 7 subjects has done sexual activity until intercourse and the rest of subject has done sexual activity until kissing the lips and holding intimate part of their partner.The subjects who conduct premarital sexual behavior begins with a sense of curiosity. So the subject of research conduct premarital sexual behavior with trial and error until they are hooked to do the activity.The closest person is very influential on sexual behavior conducted by the subject of research. Lack of parental supervision and a supportive living environment can make the study subjects feel free to engage in premarital sexual behavior.